PENERAPAN MODEL PEMBELAJARAN CTL (CONTEXTUAL TEACHER AND LEARNING) BERBANTUAN MEDIA VISUAL TERHADAP HASIL BELAJAR SISWA PADA MATERI JARINGAN TUMBUHAN - Purba, Winda; Situmorang, Masni Veronika; Silaban, Winarto (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
This study aims to determine the application of the CTL (Contextual Teacher And Learning) learning model assisted by visual media to student learning outcomes in plant tissue material for class XI at  Senior hight School  1 Sidamanik. The problem in this study is the low learning outcomes of students which are known from the results of interviews with one of the teachers in the field of biology studies at Senior hight School 1 Sidamanik. Therefore, the CTL (Contextual Teacher And Learning) learning model with the aid of visual media is applied to plant tissue material. The method in this research is quantitative, with the type of research Pre-Experimental Design and research design One Group Pret-test-Post-test design. The study population was all students of class XI semester 1 at Senior hight School  1 Sidamanik for the academic year 2022/2023, the sample of this study was class XI IPA II, which consisted of 33 students. This study uses a test instrument to measure learning outcomes before and after the study. The test used consists of 30 questions. After completing the validity test, there are 20 valid questions and 10 invalid questions. The results of the research show that the learning outcomes of students have increased. It can be seen before and after the treatment, the average value of the pre-test results an average value of 43.9. After treatment with the CTL learning model (contextualized teaching and learning), post-test scores increased by an average of 77.00. It is then analyzed using the N-Profit formula to obtain a percentage of 58.53, which falls into the "very efficient" category. Kata kunci: Hasil belajar,Model pembelajaran CTL (Contextual Teacher And Learning), Media Visual